ANTICIPATED BRAIN MOLECULAR AGING IN MAJOR DEPRESSION - Douillard-Guilloux, Gaëlle (2013)
OBJECTIVES: Brain molecular aging, the pervasive and consistent transcriptome changes associated with normal brain aging, appears to overlap with disease pathways and may be anticipated in neurodegenerative and neuropsychiatric diseases, including major depressive disorder (MDD). Here we characterize the global interaction of MDD-related gene changes with age, starting from our previous report of downregulated brain-derived neurotrophic factor (BDNF) and BDNF-dependent genes in the amygdala of women with MDD. METHODS: A large scale gene expression dataset in the amygdala from a postmortem cohort of 21 women with MDD and 21 age-matched controls (age range: 16–74 years old) was analyzed for correlations of gene transcript changes with age, in the presence or absence of a diagnosis of MDD. RESULTS: (1) The age-related decrease in BDNF transcripts observed in control subjects corresponds with further age-related decreases in BDNF and BDNF-dependent gene expression in MDD subjects; (2) most MDD-related genes are frequently age-regulated in both MDD and in control subjects; (3) the effects of MDD and age are positively correlated; (4) most genes that are age-dependent in control subjects display greater age effects in MDD subjects, and (5) the increased prevalence of age effects in MDD corresponds to similar trends in controls, rather than representing de novo age effects. CONCLUSIONS: MDD strongly associates with robust and anticipated gene expression changes that occur during normal aging of the brain, suggesting that an older molecular age of the brain represents an early biological event and/or a marker of risk for subsequent onset of MDD symptoms.